Pharmacokinetic Study of Praziquantel Enantiomers and Its Main Metabolite R-trans-4-OH-PZQ in Plasma, Blood and Dried Blood Spots in Opisthorchis viverrini-Infected Patients. - Isabel Meister; Jana Kovac; Urs Duthaler; Peter Odermatt; Jörg Huwyler; Fiona Vanobberghen; Somphou Sayasone; Jennifer Keiser (Public Library of Science (PLoS), 2016)
BACKGROUND:Praziquantel (PZQ) is the treatment of choice for infections with the liver fluke Opisthorchis viverrini, a major health problem in Southeast Asia. However, pharmacokinetic (PK) studies investigating the disposition of PZQ enantiomers (R- and S-PZQ) and its main metabolite, R-trans-4-OH-PZQ, in diseased patients are lacking. The implementation of a dried blood spot (DBS) sampling technique would ease the performance of PK studies in remote areas without clinical facilities. The aim of the present study is to provide data on the disposition of PZQ enantiomers and R-trans-4-OH-PZQ in opisthorchiasis patients and to validate the use of DBS compared to plasma and blood sampling. METHODOLOGY/PRINCIPAL FINDINGS:PZQ was administered to nine O. viverrini-infected patients at 3 oral doses of 25 mg/kg in 4 h intervals. Plasma, blood and DBS were simultaneously collected at selected time points from 0 to 24 h post-treatment. PK parameters were determined using non-compartmental analysis. Drug concentrations and areas under the curve (AUC0-24h) measured in the 3 matrices were compared using Bland-Altman analysis. We observed plasma AUC0-24hs of 1.1, 9.0 and 188.7 μg/ml*h and half-lives of 1.1, 3.3 and 6.4 h for R-PZQ, S-PZQ and R-trans-4-OH, respectively. Maximal plasma concentrations (Cmax) of 0.2, 0.9 and 13.9 μg/ml for R-PZQ, S-PQZ and R-trans-4-OH peaked at 7 h for PZQ enantiomers and at 8.7 h for the metabolite. Individual drug concentration measurements and patient AUC0-24hs displayed ratios of blood or DBS versus plasma between 79-94% for R- and S-PZQ, and between 108-122% for R-trans-4-OH. CONCLUSIONS/SIGNIFICANCE:Pharmacodynamic (PD) in vitro studies on PZQ enantiomers and R-trans-4-OH-PZQ are necessary to be able to correlate PK parameters with efficacy. DBS appears to be a valid alternative to conventional venous sampling for PK studies in PZQ-treated patients.